An unexpected postop complication. Issue 6 (1st February 2011) - Fox, A; Griffiths, T
Abstract : The case study describes a 4-year-old boy with chronic renal failure secondary to renal dysplasia, who was readmitted after re-implantation of ureters and pyeloplasty with vomiting and abdominal pain. It was diagnosed as possible bladder spasm and he was prescribed oxybutinin. This was not effective so he was prescribed baclofen in a standard dose for his age and weight (10 mg three times a day). The following day his level of consciousness deteriorated requiring admission to intensive care for supportive care including ventilation. The symptoms were caused by baclofen toxicity. The patient recovered over the next 2–3 days with no apparent long-term consequences. Baclofen is a derivative of γ-aminobutyric acid with antispastic action at a spinal level. Following oral administration the onset of action of baclofen is 30–40 min with a peak action after 2 h. Baclofen is primarily excreted by the kidney (70–85%) and has an approximate half life of 3.6 h. In this patient sequential baclofen levels were taken and found to be high. Using these levels the elimination rate constant for this patient was calculated as 0.068 and the half life was 10.2 h. This would suggest that a maximum dose of 5 mg given either once or twice a day would have been appropriate for this patient. The outcome of a root cause analysis of this incident showed that there was failure to identify a patient in renal failure needing dose adjustment. Since this incident several actions have been introduced to try and prevent a recurrence. These include identification of chronic renal failure on the prescription chart including eGFR, on-going education and training for medical staff and inclusion of eGFR in all letters and correspondence. It is hoped that this will refresh delegates' knowledge of the need to use baclofen with extreme caution in patients with renal failure and some points as to how to avoid this kind of incident.